Respuesta :
Answer:
Yes
[tex]y=e^{-11x}=\frac{1}{e^{11x}}=\frac{1}{e^{11}} \frac{1}{e^x}=\frac{1}{e^{11}} e^{-x}[/tex]
So then we see that the base on this case is: [tex]c=\frac{1}{e^{11}}[/tex] , so then our function can be considered as an exponential function.
Step-by-step explanation:
First we need to define an exponential function.
The exponential function with a base c is givn by the following expression:
[tex]f(x)=c^x[/tex], and [tex]c>0, c\neq 1[/tex] and x can be any real number.
The exponential function have always a base and a variable. The value c it's called the base and x the variable.
The exponential function is defined as:
[tex]y=e^x[/tex]
And the function given by:
[tex]y=\frac{1}{e^x} [/tex] is called the natural exponential function.
For our special case our function is given by:
[tex]y=e^{-11x}=\frac{1}{e^{11x}}=\frac{1}{e^{11}} \frac{1}{e^x}=\frac{1}{e^{11}} e^{-x}[/tex]
So then we see that the base on this case is: [tex]c=\frac{1}{e^{11}}[/tex] , so then our function can be considered as an exponential function.